Can the thermal expansion be controlled by varying the hydrogen bond dimensionality in polymorphs?. (16th March 2015) - Saraswatula, Viswanadha G.; Bhattacharya, Suman; Saha, Binoy K.
Abstract : A higher dimensional (1-D) hydrogen bonded form shows smaller thermal expansion than a lower dimensional (0-D) hydrogen bonded form of 2-butynoic acid. Abstract : 2-Butynoic acid exists in two enantiotropically related polymorphic forms. The monoclinic form, containing a one dimensional hydrogen bond in the structure, exhibits a smaller volumetric thermal expansion coefficient than the triclinic form which has a zero dimensional hydrogen bond. The phase transformation 1D → 0D has been correlated with the different thermal expansion abilities of the groups present in the molecule and the crystal packing in these two forms.